Encouraging and Enabling a Science-Based Approach to Ecological Restoration - Kirsty Shaw (Sibbaldia, 2015)
Botanic gardens harbour many of the skills necessary for undertaking ecological restoration. This includes strong horticultural and taxonomic expertise, seed collection, conservation and propagation skills, the ability to design and lead monitoring programmes, as well as providing training and outreach to the public. This unique set of skills is rarely found within other institutions. Many of the world’s botanic gardens share a common mission: to secure plant diversity, working within the framework of national and international policies. Botanic gardens are therefore not only well-placed to lead ecological restoration initiatives, but it is their goal and responsibility to apply their knowledge, expertise and skills to addressing ecological degradation.